Business intelligence : 6th European Summer School, eBISS 2016, Tours, France, July 3-8, 2016, Tutorial lectures - Marcel, Patrick; Zimányi, Esteban (Springer, 2017)
This book constitutes the tutorial lectures of the 6th European Business Intelligence Summer School, eBISS 2016, held in Tours, France, in July 2016. Tutorials were given by renowned experts and covered recent and various aspects of Business Intelligence and Big Data. This volume contains the lecture notes of the summer school.
Keywords: Management information systems -- Congresses.; Business -- Data processing -- Congresses.; Data mining -- Congresses.; Business intelligence -- Congresses.; elektronické knihy; electronic books